Benefícios da suplementação de selênio na prevenção e no tratamento do câncer - Brondani, Camila Kich (Universidade do Vale do Rio dos Sinos, 2011)
Recent studies report that individuals with cancer benefit from this mineral supplementation specially in subjects with low levels of selenium (Se) in plasma. A systematic review was performed aimed at analizyng the effectiveness of Se supplementation in the prevention and treatment of Cancer. The search was carried out in the Pubmed, BIREME and Cochrane databases, comprising the last 15 years, and only randomized studies were selected. All analyzed trial used selenium supplementation in adults. The review studies showed evidence that the use of Se in cancer prevention and treatment have positive results and higher prevalence in individuals with low plasma levels. Extending studies to determine the effectiveness of Se supplementation is imperative , taking into account the genetic predisposition of individuals .
Keywords: Selênio; Câncer; Selenium; Cancer